Menggali Potensi Desa Nelayan dalam Meningkatkan Kesejahteraan Masyarakat pada Desa Marunda Kecamatan Cilincing Jakarta Utara - Edhie Budi Setiawan; Heri Subagyo; Aditya Wardhana; Sekar Widyastuti Pratiwi (Institut Transportasi dan Logistik Trisakti, 2022)
The Independent Village in Marunda, which is located on the coast, has the potential as a potential shark producer to be developed. Markets that need to be open are wide enough, including the need for catering, and modern markets such as Makro, Transmart and others. To enter a wide market requires special attention, especially with product health and hygiene (hygenic) and product quarantine. The purpose of this activity is to improve the welfare of the community in Marunda village, Cilincing sub-district, North Jakarta through socialization on how to maintain product health and hygiene (hygenic) and product quarantine. This socialization was carried out offline at PT XYZ which was attended by the owners, employees and students of ITL Trisakti in the context of implementing MBKM. The results of the socialization are expected to be carried out to expand the market and increase the amount of production.